2020
DOI: 10.1038/s41598-020-78040-8
|View full text |Cite
|
Sign up to set email alerts
|

Cattle mitogenome variation reveals a post-glacial expansion of haplogroup P and an early incorporation into northeast Asian domestic herds

Abstract: Surveys of mitochondrial DNA (mtDNA) variation have shown that worldwide domestic cattle are characterized by just a few major haplogroups. Two, T and I, are common and characterize Bos taurus and Bos indicus, respectively, while the other three, P, Q and R, are rare and are found only in taurine breeds. Haplogroup P is typical of extinct European aurochs, while intriguingly modern P mtDNAs have only been found in northeast Asian cattle. These Asian P mtDNAs are extremely rare with the exception of the Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Until recently, only several ancient or historical P haplotypes were documented in GenBank: British aurochs Pre‐Neolithic (6.7 kyBP; GU985279); historical Polish aurochs (1.5 kyBP; JQ437479); three historical ‘Danish’ aurochs (MF169211, MF169212 and MF169213; all 0.6 kyBP); and one modern cattle (Korean beef cattle sample DQ124389). After all our mitogenome analyses were completed, 14 individuals with haplotypes several mutations away from the Korean sequence DQ124389 were found in the Japanese Shorthorn (Mannen et al, 2020 ) and one in Chinese (Yanbian) individual (Xia et al, 2021 ). In the MJN (Figure 2c and Figure S1 ), the P haplotype found in Murbodner cattle (MZ901404‐08) was closest (11 mutations) to the reference Pre‐Neolithic aurochs (GU985279).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, only several ancient or historical P haplotypes were documented in GenBank: British aurochs Pre‐Neolithic (6.7 kyBP; GU985279); historical Polish aurochs (1.5 kyBP; JQ437479); three historical ‘Danish’ aurochs (MF169211, MF169212 and MF169213; all 0.6 kyBP); and one modern cattle (Korean beef cattle sample DQ124389). After all our mitogenome analyses were completed, 14 individuals with haplotypes several mutations away from the Korean sequence DQ124389 were found in the Japanese Shorthorn (Mannen et al, 2020 ) and one in Chinese (Yanbian) individual (Xia et al, 2021 ). In the MJN (Figure 2c and Figure S1 ), the P haplotype found in Murbodner cattle (MZ901404‐08) was closest (11 mutations) to the reference Pre‐Neolithic aurochs (GU985279).…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of P 2 haplotypes in modern cattle in North‐east Asia and Japan assigned to haplogroup P 2 (DQ124389 and related sequences) also provides little evidence for the pattern of cattle domestication during Neolithization in Europe. With the exception of Japanese Shorthorn, haplogroup P 2 (P 1a in Mannen et al, 2020 ) is extremely rare and has only been found in two ~0.6‐kyBP‐old aurochs’ samples (MF169211 and MF169212) in northern Europe (Figure S1 ). Interestingly, P 2 is very similar to haplogroup T 3 at the amino acid level (Figure S5 B).…”
Section: Discussionmentioning
confidence: 99%
“…The mtDNA haplogroup P was once the most common haplogroup in European aurochs according to surveys of ancient DNA (Edwards et al, 2007 ), but it has not been detected in modern cattle in Europe or in other Japanese Wagyu breeds. However, the mtDNA haplogroup P has been identified at a high frequency in Japanese Shorthorn cattle, indicating that the propagation root of Nambu‐ushi differs from that of other Japanese native cattle (Mannen et al, 2020 ; Noda et al, 2018 ). Uemoto et al ( 2017 ) and Sasago et al ( 2018 ) also identified the allele frequencies of beef palatability genes in four breeds (Japanese Black, Japanese Brown, Japanese Shorthorn, and Holstein), and those of the Japanese Shorthorn were completely different from those of the other three breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese Shorthorn has a unique genetic background compared to that of other Japanese Wagyu breeds (Mannen et al, 2020 ; Noda et al, 2018 ), and the maintenance of genetic diversity is important for future genetic resources. For example, some consumers prefer lean meat, as their needs have diversified (Sasaki et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is growing evidence that the domestication of Chinese cattle was a non-native process, the increasing excavation of auroch remains has made the origin of Chinese cattle contentious. Particularly, the exist of haplogroup C auroch 10,000 years ago in Northeast China ( Zhang et al, 2013 ) and the evidence of haplogroup (P1a) incorporated into domestic cattle of northeastern Asia ( Mannen et al, 2020 ) make it necessary to determine the species and phylogenetic relationships among suspected bovine remains from different sites in China, as well as to define the role that aurochs play in the development of taurine cattle in China.…”
Section: Introductionmentioning
confidence: 99%